Juridical Review of Protection for Victims of Minor Sexual Violence - Indah Gita Cahyani; R Rizka (Universitas Muhammadiyah Surakarta, 2023)
The aim of this research is to identify legal protection for child victims of sexual crimes. An empirical research approach was applied in this research. According to the findings of this study, legal protection for child victims of sexual relations crimes is provided with the aim of protecting victims, especially victims of sexual relations, to obtain their rights as victims through providing health services to children in an effort to restore the situation of children as victims of sexual relations. sexual. Children also receive legal protection in the form of legal aid, rehabilitation and prevention. There is a need for fair criminal legal solutions for victims of sexual relations, which add to or take into account the rights of victims of sexual relations, and parents must participate in efforts to provide protection for children by fulfilling children's rights, protecting children's best interests, and increasing supervision. towards children.